Realization of Promises in an English as a Foreign Language Conversation Class - Kartikasari, Kartikasari (Lembaran Ilmu Kependidikan, 2016)
This study was aimed at analyzing kinds of promise strategies realized by the students of an EFL conversation class at LBPP LIA Semarang Candi. The objectives were to find out whether the promise strategies are realized by the respondents, to describe the kinds of promise strategies applied by the students, to find out the probable factors influencing the realization of promise and to explain the reasons behind it. This research is qualitative, descriptive. The data was gathered by two methods: DCT and role play. In conducting the research, the steps were transcribing the data, coding the data, classifying the data, interpreting the data, describing the finding and drawing the conclusions. In this research, I analyzed two kinds of data from from ten students, consisting 12 DCT situations and 12 role play situations with integrated probable factors (dominance, relationship and imposition). Future-action is the most realized promise strategy. Non-strategy and promise-to-act came after that, while predictive-assertion is the least realized promise strategy. In conclusion, studentsâ schemata resulting from the language learning process and their mother tongue, language transfer and their maturity influence the realization of promise strategy more than dominance, distance and imposition.